Teacher Students’ Critical Literacy in the Academic Environment - Okta Rosfiani; Tanti Sri Kuswiyanti; Mohamed Metwaly Abdultawab (TARBIYA: Journal of Education in Muslim Society, 2021)
AbstractIn an academic setting, critical literacy necessitates that teacher-students be critical of every text message (textbooks, videos, films, and other electronic media) that they read from courses. This study aims to illustrate the critical literacy of teacher students in an academic college environment in Jakarta, Indonesia, describing how critical literacy becomes a habit, a need, and eventually becomes a teacher-student culture. This case study employs a qualitative technique with an ethnographic design. Purposive sampling is used in this study. The research participants were a group of 14 female and two male teacher-students from the Madrasah Ibtidaiyah Teacher Education study program. Observation and documentation are used to collect research data. Observer becoming an insider who participates in critical literacy exercises in the classroom. Portfolios, notes on critical literacy activities, assignments, midterm exam scores, and final exam scores are among the documents gathered. According to the findings of this study, we should first put up an online platform scaffolding for critical literacy. Second, it demands significant encouragement from lecturers at the start of students' teaching preparation program, as well as commitment from lecturers and teacher students. Third, teamwork among lecturers in the study program is required. Fourth, critical discussions must be constructed using multiple narratives from scholarly papers and social media texts.AbstrakDalam lingkungan akademik, literasi kritis mengharuskan guru-siswa bersikap kritis terhadap setiap pesan teks (buku teks, video, film, dan media elektronik lainnya) yang mereka baca dari kursus. Penelitian ini bertujuan untuk menggambarkan literasi kritis siswa guru di lingkungan akademik perguruan tinggi di Jakarta, Indonesia, menggambarkan bagaimana literasi kritis menjadi kebiasaan, kebutuhan, dan akhirnya menjadi budaya guru-siswa. Studi kasus ini menggunakan teknik kualitatif dengan desain etnografi. Purposive sampling digunakan dalam penelitian ini. Partisipan penelitian ini adalah sekelompok 14 orang guru-murid laki-laki dan perempuan dari program studi Pendidikan Guru Madrasah Ibtidaiyah. Observasi dan dokumentasi digunakan untuk mengumpulkan data penelitian. Observer menjadi orang dalam yang mengikuti latihan literasi kritis di kelas. Portofolio, catatan kegiatan literasi kritis, tugas, nilai ujian tengah semester, dan nilai ujian akhir termasuk di antara dokumen yang dikumpulkan. Menurut temuan penelitian ini, pertama-tama kita harus memasang perancah platform online untuk literasi kritis. Kedua, menuntut dorongan yang signifikan dari dosen di awal program persiapan mengajar mahasiswa, serta komitmen dosen dan mahasiswa guru. Ketiga, kerjasama antar dosen di prodi sangat diperlukan. Keempat, diskusi kritis harus dibangun dengan menggunakan narasi ganda dari karya ilmiah dan teks media sosial. How to Cite: Rosfiani, O., Kuswiyanti, T.S., Abdultawab, M. M. (2021). Teacher Students’ Critical Literacy in the Academic Environment. TARBIYA: Journal of Education in Muslim Society, 8(2), 179-189. doi:10.15408/tjems.v8i2.24095.